72.0k views
0 votes
Solve for y:

Y^2-2xy=1

User PratsJ
by
5.1k points

1 Answer

5 votes

Answer:

y = x ±√(x²+1)

Explanation:

Rewrite to standard quadratic form, then use the quadratic formula.

... y² -2xy -1 = 0

... a=1, b=-2x, c=-1, so the quadratic formula

... y = (-b ±√(b²-4ac))/(2a)

can be filled in as ...

... y = -(-2x) ±√((-2x)² -4(1)(-1)))/2(1))

... y = x ±√(x² +1)

For any given value of x, there are two possible values of y. This is not a function.

User Speedogoo
by
5.2k points